Study of the heavy molecular states in the quark model with meson exchange interaction - 余思海 王保凯 陈晓林 邓卫真 (Chinese physics C, 2012)
Some charmonium-like resonances such as X（3872） can be interpreted as possible D （＊）  （＊） molecular states.Within the quark model,we study the structure of such molecular states and the similar B （＊）  （＊） molecular states by taking into account the light meson exchange （π,η,ρ,ω and σ） between two light quarks from different mesons.